2022
DOI: 10.1007/s11356-022-19580-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of economic development, income inequality, transportation, and environmental expenditures on transport emissions: evidence from OECD countries

Abstract: Environmental quality has been pondered as an essential aspect of sustainable development across the global economies. Several factors such as economic development, income inequality, transportation, and environmental expenditures drastically influence environmental quality. More specifically, the transport sector is a major contributor to carbon emissions which deteriorate the environmental quality. Therefore, this study investigates whether economic development, transportation, environmental expenditures, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…According to the health expenditure theory, factors affecting health expenditure can generally be divided into two main categories: income factors and nonincome factors. Among them, income factors mainly include economic growth [14,15]. Non-income factors are mainly classified into six primary categories, namely:…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…According to the health expenditure theory, factors affecting health expenditure can generally be divided into two main categories: income factors and nonincome factors. Among them, income factors mainly include economic growth [14,15]. Non-income factors are mainly classified into six primary categories, namely:…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…Li (2014) pointed out that high economic expansion should not simply pursue economic aggregate and growth rate, but should pay more attention to the harmonious growth of economy, society and environment. Hussain et al (2022) found that the consumer price index (CPI) factors that lead to the decline of Jing-Jin-Ji market integration development level are mainly housing, clothing, transportation and communication.…”
Section: Related Workmentioning
confidence: 99%
“…Economic progress has long been considered the primary driver of environmental pollution (Alvarado et al, 2021b). Evidently, growth in almost every economy is fueled by energy (Alvarado et al, 2019), and the energy structure of most countries is constituted of fossil energy up to a great extent (Kanat et al, 2021;Oláh et al, 2021;Štreimikienė, 2021;Hussain et al, 2022b). Hence, it is not surprising that growth levels are closely knotted with environmental pollution (Ahmed et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%